Complement Activation in Autoimmune Bullous Dermatoses: A Comprehensive Review - Edwards, Gareth; Diercks, Gilles F. H.; Seelen, Marc A. J.; Horvath, Barbara; van Doorn, Martijn B. A.; Damman, Jeffrey (Frontiers in Immunology, 2019)
Autoimmune bullous dermatoses (AIBD) are characterized by circulating autoantibodies that are either directed against epidermal antigens or deposited as immune complexes in the basement membrane zone. The complement system (CS) can be activated by autoantibodies, thereby triggering activation of specific complement pathways. Local complement activation induces a pathogenic inflammatory response that eventually results in the formation of a sub- or intraepidermal blister. Deposition of complement components is routinely used as a diagnostic marker for AIBD. Knowledge from different animal models mimicking AIBD and deposition of complement components in human skin biopsies provides more insight into the role of complement in the pathogenesis of the different AIBD. This review outlines the role of the CS in several AIBD including bullous pemphigoid, epidermolysis bullosa acquisita, mucous membrane pemphigoid, pemphigus, linear IgA-diseases and dermatitis herpetiformis. We also discuss potential therapeutic approaches targeting key complement components, pathways and pathogenic complement-mediated events.